2019
DOI: 10.1111/1348-0421.12685
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa infection stimulates mitogen‐activated protein kinases signaling pathway in human megakaryocytes

Abstract: Pseudomonas aeruginosa is a major cause of nosocomial infections and contributes to higher mortality in hospitalized individuals. Infection by P. aeruginosa triggers host immune response through activation of pathogen recognition receptors, which are present in innate cells. Several studies have reported the mechanism of P. aeruginosa induced innate immunity in multiple cell types. But so far there is no reports on response of megakaryocytes to P. aeruginosa infection. Hence, our aim was to investigate the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Herein, JNK pathway was downregulated by PAO1 BCM, with a concomitant decrease in c-Jun levels. Similar to this dissertation, P. aeruginosa has been reported to exploit kinase pathways as well by inducing apoptosis in human conjunctiva epithelial cells and human megakaryocytes through JNK pathway activation (Gopala Krishnan et al, 2019;Jendrossek et al, 2001). Additionally, Losa et al (2014) have reported that apoptosis induced in airway epithelial cells by P. aeruginosa is caused by increased gap junction expression and this increase in gap junction is regulated by JNK signalling inhibition.…”
Section: Discussionsupporting
confidence: 58%
“…Herein, JNK pathway was downregulated by PAO1 BCM, with a concomitant decrease in c-Jun levels. Similar to this dissertation, P. aeruginosa has been reported to exploit kinase pathways as well by inducing apoptosis in human conjunctiva epithelial cells and human megakaryocytes through JNK pathway activation (Gopala Krishnan et al, 2019;Jendrossek et al, 2001). Additionally, Losa et al (2014) have reported that apoptosis induced in airway epithelial cells by P. aeruginosa is caused by increased gap junction expression and this increase in gap junction is regulated by JNK signalling inhibition.…”
Section: Discussionsupporting
confidence: 58%
“…A total of 3–6 µg of antibody was used per immunoprecipitation, and antibody–protein complexes were collected with 50–75 µl protein A‐Sepharose. Western blotting was performed, as previously described …”
Section: Methodsmentioning
confidence: 99%